Research on Optimization of Pooling System and Its Application in Drug Supply Chain Based on Big Data Analysis - DengFeng Wu; Hongyi Mao (International Journal of Telemedicine and Applications)
Reform of drug procurement is being extensively implemented and expanded in China, especially in today’s big data environment. However, the pattern of supply mode innovation lags behind procurement improvement. Problems in financial strain and supply break frequently occur, which affect the stability of drug supply. Drug Pooling System is proposed and applied in a few pilot cities to resolve these problems. From the perspective of supply chain, this study analyzes the process of setting important parameters and sets out the tasks of involved parties in a pooling system according to the issues identified in the pilot run. The approach is based on big data analysis and simulation using system dynamic theory and modeling of Vensim software to optimize system performance. This study proposes a theoretical framework to resolve problems and attempts to provide a valuable reference for future application of pooling systems.